Implementasi Praktik Pembelajaran Partuturon terhadap Penanaman Nilai-nilai Kasih Sayang Peserta Didik - Fitri Arfah; Nurul Padhilah; Amelia Amelia; Putri Riskiyah (Prodi Pendidikan Keagamaan Islam, 2022)
Character education is an essential aspect of shaping students' personalities, particurly in instilling the value of compassion from an early age. This study aims to examine the implementation of partuturon learning practices in fostering students’ compassion values at SD Negeri 302 Aek Garingging. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The results showed that the implementation of partuturon learning practices has been carried out effectively through role-playing methods, student grouping, and reinforcement of compassion values. The main supporting factors include strong local wisdom, teachers’ commitment, and students’ enthusiasm. However, the study also found several challenges, such as the lack of understanding of the philosophical meaning of partuturon and limited learning media. Despite these challenges, partuturon remains an effective approach to instilling compassion values in elementary school students.